Malaysian politics post-GE13 : the deracialisation of BN? - Yang Razali Kassim (2014)
In the wake of the mixed results of the recent general election, the ruling coalition, Barisan National (BN), has been thrown into a state of introspection. Early signs point to a fundamental rethink of its identity as a race-based coalition.